Politicians’ views on societal responsibility and possibility to promote newly arrived migrants’ health in Sweden - Svanholm, Sara; Carlerby, Heidi; Viitasara, Eija (Health Promotion International, 2023)
Newly arrived migrants in Sweden risk facing ill health. Politicians at the local and regional levels are involved in many decisions regarding the social determinants of health. The aim of this study was to explore politicians’ views on different societal actors’ responsibility and possibility to promote newly arrived migrants’ health. Data were collected through online questionnaires completed by 667 politicians from municipality and regional councils in northern Sweden. Bivariate analysis was performed using the Wilcoxon signed-rank test. Multivariate analyses were performed using cluster analysis and binary logistic regression analysis. The results show that politicians generally rate societal actors’ responsibility and possibility to promote the general population’s health higher than newly arrived migrants’ health. Moreover, they consider societal actors’ responsibility to be greater than their possibility to promote health. Factors significantly contributing to politicians’ high ratings of societal responsibility and possibility are attitude (odds ratio [OR] = 2.156, 95% confidence interval [CI]: 1.306–3.558), specific knowledge of newly arrived migrants’ health status (OR = 1.528, 95% CI: 1.005–2.323), personal interest in public health (OR = 2.452, 95% CI: 1.460–4.119), being a municipality politician (OR = 1.659, 95% CI: 1.031–2.670) and being female (OR = 1.934, 95% CI: 1.333–2.806). This study shows that politicians generally rate societal responsibility and possibility to promote newly arrived migrants’ health rather high. Personal characteristics are important for politicians’ high or low ratings of responsibility and possibility, suggesting insufficient structural support for politicians in health promotion.